Effects of the Built Environment on Travel-Related CO2 Emissions Considering Travel Purpose: A Case Study of Resettlement Neighborhoods in Nanjing - Yiwen Zhang; Wenzhu Zhou; Jiayi Ding (Buildings, 2022)
With rapid urbanization, an increasing number of resettlement housing neighborhoods have been developed in suburbs in China. Such neighborhoods often face problems of spatial mismatch (jobs–housing and daily life), excessive street scale, and inconvenient transportation, which directly and indirectly lead to long travel distances and higher travel carbon emissions for residents. Understanding how to improve the built environment of resettlement housing and thus influence travel CO2 emissions is essential to guide low-carbon travel and reduce greenhouse gas emissions. Based on an electronic questionnaire and travel carbon emission measurements collected in 12 resettlement housing neighborhoods in Nanjing in 2022, this study used a three-group structure equation model (SEM) to measure the impact of resettlement housing’s built environment on travel CO2 emissions from commutes, housework trips, and recreational trips. It was found that the improvement of destination accessibility can significantly reduce the carbon emissions of residents’ trips. Second, the built environment of resettlement housing can affect travel carbon emissions through mediator variables and direct effects. In addition, these effects show different paths and sizes depending on the purpose of the travel trip. These results are significant for the planning and construction of resettlement houses and offer guidance for low-carbon travel.